A Dual‐Band Bandpass Filter Using Capacitively I/O Coupling. Issue 8 (28th May 2013) - Lee, Jahyeon; Lim, Yeongseog
ABSTRACT A compact microstrip dual‐band bandpass filter with good frequency selectivity was proposed. The proposed dual‐band bandpass filter is configured with two dual‐mode resonator and skew‐symmetrically coupled capacitively input/output coupling. By using these input/output coupling structure, extra transmission zeros can be generated. The dual‐band bandpass filter is designed for 2.4/5.2 GHz WLAN. Experimental measurements are also presented for the validation of the theory. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1823–1825, 2013